2021
DOI: 10.1111/resp.14056
|View full text |Cite
|
Sign up to set email alerts
|

High turnover of types III and VI collagen in progressive idiopathic pulmonary fibrosis

Abstract: Background and objective Prediction of idiopathic pulmonary fibrosis (IPF) progression is vital for the choice and timing of treatment and patient follow‐up. This could potentially be achieved by prognostic blood biomarkers of extracellular matrix (ECM) remodelling. Methods Neoepitope biomarkers of types III and VI collagen turnover (C3M, C6M, PRO‐C3 and PRO‐C6) were measured in 185 patients with newly diagnosed IPF. Disease severity at baseline and progression over 6 months was assessed by lung function tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
2
14
1
Order By: Relevance
“…Since our data suggest that patients with a higher baseline type I and III collagen turnover have a higher risk of disease progression, it would be interesting to make a direct comparison of C1M and PRO-C3 with the above-mentioned biomarkers to verify if they could perform better. Interestingly, we have recently shown that degradation of type III collagen (C3M) was related to disease severity at the time of diagnosis [28]. However, in the present analyses, it was not related to increased risk of progression, indicating that C3M is more associated with disease severity rather than being a prognostic biomarker in this population.…”
Section: Discussioncontrasting
confidence: 73%
See 2 more Smart Citations
“…Since our data suggest that patients with a higher baseline type I and III collagen turnover have a higher risk of disease progression, it would be interesting to make a direct comparison of C1M and PRO-C3 with the above-mentioned biomarkers to verify if they could perform better. Interestingly, we have recently shown that degradation of type III collagen (C3M) was related to disease severity at the time of diagnosis [28]. However, in the present analyses, it was not related to increased risk of progression, indicating that C3M is more associated with disease severity rather than being a prognostic biomarker in this population.…”
Section: Discussioncontrasting
confidence: 73%
“…This may be explained by the fact that C1M is generated with different matrix metalloproteinases (MMP-2, -9 and -13) and C3M is only generated with MMP-9, what may clarify the reason why C1M is related to progression and C3M is not. Degradation of type I collagen (C1M) and formation of type III and VI collagen (PRO-C3 and PRO-C6) have consistently been shown to be promising biomarkers for disease progression and these biomarkers may reflect and predict fibrotic changes in the lung [15,16,28]. We hope future studies will validate our findings.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…High baseline serum concentrations of collagen formation biomarkers, PRO-C3 and PRO-C6, were also associated with more rapid disease progression (≥ 10% FVC decline or death) [ 9 ]. The latter findings were consistent with results from the PFBIO cohort, a real-world cohort of Danish patients with mild IPF (n = 185, baseline mean [SD] percent predicted FVC 89.7% [19.3]) [ 10 ].…”
Section: Discussionsupporting
confidence: 86%
“…Neoepitope biomarkers can be used to assess ECM remodeling in fibrotic conditions such as IPF [ 6 , 7 ]; these neoepitope biomarkers measure newly formed epitopes that may be generated by removal of collagen propeptides (reflecting protein formation) or by specific protease-mediated cleavage of mature proteins (reflecting protein degradation). Multiple longitudinal studies have demonstrated that elevated serum levels of these biomarkers are associated with poor prognosis in IPF [ 8 10 ].…”
Section: Introductionmentioning
confidence: 99%